Efficiency study on a new progressive freeze concentration system for freeze wastewater treatment - Jusoh, Mazura; Mohd. Yunus, Rosli; Abu Hassan, Mohd. Ariffin (Penerbit UTM Press, 2008)
A newer method of freeze concentration, progressive freeze concentration (PFC) was used on glucose solution as simulated wastewater to concentrate and treat it. PFC is hoped to be able to compensate for the disadvantages of the conventional suspension freeze concentration. In PFC, ice crystals were formed as a layer on the designed heat exchanger surface instead of in a suspension. In this particular research, a helical structured copper crystallisation chamber was designed and fabricated. The effect of three operating conditions on the performance of the newly designed crystallisation chamber was then investigated, which are the initial circulation flowrate, concentration of solution and coolant temperature. The performance of the design was evaluated by the effective partition constant, K, calculated from the volume and concentration of the solid and liquid phase. The system was also monitored by a data acquisition tool in order to see the temperature profile throughout the process. On completing the experimental work, it was found that higher flowrate resulted in a lower K, which translated into high efficiency. The efficiency is the highest at 1000 ml/min. It was also discovered that the initial concentration of solution highly affected the purity of the final ice crystals formed. The process also gives the highest efficiency at a coolant temperature of â€“6 Â°C.